Aquifer Assessment in the Capit Urang Tourist Area, Metro City: A Vertical Electrical Sounding Approach - Josua Nico Batistuta Sihombing; Kemas Daffa Hendriyastama; Andreas Sipahutar; Risky Martin Antosia (Program Studi Fisika Universitas Negeri Jakarta, 2026)
This study was conducted in the Capit Urang Tourist Area, Metro City, which is surrounded by rivers and faces problems with turbid well water that cannot be directly used. The research aims to identify subsurface conditions, especially aquifer thickness and depth, and to evaluate the possibility of deeper aquifers with better water quality. The Vertical Electrical Sounding (VES) method with a Schlumberger array was applied at six sounding points with a maximum AB/2 spacing of 100 m. Data were acquired using a Naniura resistivity meter, processed into apparent resistivity, and inverted with IPI2Win software. The results indicate four main subsurface layers with a resistivity pattern of ρ₁ < ρ₂ > ρ₃ < ρ₄. The first layer has a resistivity of 50–150 Ωm and is interpreted as topsoil with a thickness of less than 1.5 m. The second layer has a resistivity of 300–400 Ωm and is interpreted as gravel to a depth of about 6 m. The third layer, with resistivity of 40–70 Ωm, is interpreted as sandstone functioning as an aquifer with a thickness of 10–13 m to a depth of roughly 16 m. The fourth layer, with resistivity of 160–650 Ωm, is interpreted as impermeable bedrock. The aquifer is influenced by river infiltration, leading to turbid groundwater, while the limited electrode span prevented detection of deeper aquifers. Based on lithological interpretation, the aquifer system is classified as an unconfined to semi-unconfined aquifer. These findings provide a scientific basis for groundwater management and for future hydrogeophysical and hydrochemical investigations to improve water-supply sustainability in the Capit Urang Tourist Area.